Restorative Justice in Contemporary Criminal Law: Comparative Perspectives and Emerging Trends - salim, Andre; santosa, Tomi Apra; Ghoni, Abdul; Kadir, Taqiyuddin; Wijoyo, Hadion (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study analyzes the concept of restorative justice in contemporary criminal law by highlighting comparative perspectives and current trends that are developing in various jurisdictions. Using a qualitative approach based on literature studies, this study searches academic literature, laws and regulations, and international and national court decisions to identify patterns of policy implementation and innovation. The results of the analysis show that restorative justice is increasingly integrated as an alternative to punishment that emphasizes the recovery of victims' losses, perpetrator participation, and social reconciliation, while challenging the dominant retributive paradigm. A comparison of practices in Europe, North America, and Asia shows significant variations in legal frameworks, mediation mechanisms, and institutional support, influenced by cultural and political contexts. In addition, global trends such as the digitization of the mediation process and the involvement of local communities are expanding the scope of restorative justice implementation, but still face challenges related to procedural standards and the protection of the rights of the parties involved. This study recommends strengthening regulations, enhancing facilitator capacity, and cross-border empirical research to ensure the effectiveness and sustainability of restorative justice implementation in the modern criminal justice system. These findings are expected to make a theoretical and practical contribution for policymakers, academics, and legal practitioners in designing criminal policies that are more humane and responsive to the needs of society.